Mycorrhizal association in soybean and weeds in competition - Fialho, Cíntia Maria Teixeira; Silva, Gustavo Soares da; Faustino, Laís Araújo; Carvalho, Felipe Paolinelli de; Costa, Mauricio Dutra; Silva, Antonio Alberto da (Acta Scientiarum. Agronomy, 2016)
The purpose of this study was to evaluate the effects of mycorrhizal association on the interference of Bidens pilosa, Urochloa decumbens and Eleusine indica on soybean culture in two conditions: a) plants competing without contact with roots of another species; b) with contact between roots. At 60 days after planting, growth, nutrient accumulation and mycorrhizal colonization of soybean and weeds were evaluated. The contact between roots of soybean plant and weed species increased the negative interference effects for both species, with less growth and nutrient accumulation. With the individualization of roots, higher competition occurred for soil resources up to 60 days of coexistence between species. In competition with soybean, Bidens pilosa and Urochloa decumbens stood out in accumulation of most nutrients without differing from when cultivated in monocultivation. The increase of the soybean mycorrhizal colonization was 53, 40 and 33% when in competition with Urochloa decumbens, Eleusine indica and Bidens pilosa species, respectively. A positive interaction occurred for soybean mycorrhizal colonization and competing plants irrespective of weed species or root contact.